Analysis of Socio-Economic Factors Affecting the Success of Catfish Farming in Tarpaulin Pools in Selebar District, Bengkulu City - Andika Nurohim; Herri Fariadi; Ana Nurmalia (Jurnal Multidisiplin, 2026)
Catfish farming not only reflects the economic activities of the community but also represents the dynamics of interactions between social, economic, and environmental aspects. The purpose of this rsearch is to analyze the success rate of catfish farming in tarpaulin ponds and to analyze the socio-economic factors that influence the success of catfish farming in tarpaulin ponds. The method used is quantitative research, data collected from primary and secondary data. With a sample of 23 catfish entrepreneurs in Selebar District, Bengkulu City using census techniques. Data were analyzed descriptively to determine the level of success and used multiple linear regression analysis to test the effect of independent variables on the dependent variable. The results of this study indicate that the success rate of catfish farming in tarpaulin ponds in Selebar Sub-District, Bengkulu City is in the "very high" category with an average score of 29.8. Socioeconomic factors influencing the success of catfish cultivation in tarpaulin ponds in Selebar District, Bengkulu City are business capital (X1), farmer education and knowledge (X2), institutional support (X3), and community social conditions (X6). While variables that do not influence this are access to information and cultivation technology (X4), marketing (X5), and selling price (X7).